Seasonal deformation monitoring over thermokarst landforms using terrestrial laser scanning in Northeastern Qinghai-Tibetan Plateau - Wen Zhong; Tingjun Zhang; Jie Chen; Jianguo Shang; Shufa Wang; Cuicui Mu; Chengyan Fan (International Journal of Applied Earth Observation and Geoinformation, 2021)
Climate warming has accelerated permafrost degradation over the Qinghai-Tibet Plateau (QTP) over the past several decades. The development of thermokarst landforms is a key indicator of permafrost degradation, while it lacks quantified measurements and comprehensive research over the QTP. The aim of this study is to investigate the development of thermokarst terrains through repeated ground-based elevation observations by using terrestrial laser scanning (TLS) in the northern QTP from April 11, 2016 through June 16, 2018. TLS Time series analysis reveals that the margin of the thermokarst landforms undergoes significant ground subsidence, side materials collapse, and/or uplift and deposit, especially in the southeastern, northwestern part of thermokarst landforms during the middle through the late thaw season. The vertical deformation and headwall retreat of thermokarst landforms reached −3.364 m and 10.66 m from April 11, 2016 to June 16, 2018, respectively. We also generated high-resolution orthophotos based on aerial photos acquired by the built-in 4 K RGB (red, green, blue) camera of DJI Phantom 3 Professional unmanned aerial vehicle (UAV) in April and October of 2016. The UAV images confirmed the TLS observations during the same period and presented the severely deformed area. This study reveals that the seasonal vertical deformation and headwall retreat of the thermokarst landforms in the study site are consistent with seasonal ground temperature change during the observed period. Extreme precipitation event as a key factor triggered the severe deforming of the case study thermokarst. Ground ice, peat layer, and human activity also contributed to the thermokarst landforms formation. The results also illustrate that TLS is an effective method for studying thermokarst development quantitatively.